2011
DOI: 10.1016/j.aop.2011.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Bogolyubov-Valatin transformations: Two modes

Abstract: Extending our earlier study of nonlinear Bogolyubov-Valatin transformations (canonical transformations for fermions) for one fermionic mode, in the present paper we perform a thorough study of general (nonlinear) canonical transformations for two fermionic modes. We find that the Bogolyubov-Valatin group for n = 2 fermionic modes which can be implemented by means of unitary SU (2 n = 4) transformations is isomorphic to SO(6; R)/Z 2 . The investigation touches on a number of subjects. As a novelty from a mathem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 198 publications
(295 reference statements)
0
6
0
Order By: Relevance
“…Finally, in the approach taken here, it will be possible to consider transformations that mix the two Hilbert spaces, which will be further explored. As special cases of transformed basis sets, one could or more general nonlinear canonical transformations [97]. Some general results on canonical transformations are reviewed in appendix C.1.…”
Section: Optimized Basis Setmentioning
confidence: 99%
“…Finally, in the approach taken here, it will be possible to consider transformations that mix the two Hilbert spaces, which will be further explored. As special cases of transformed basis sets, one could or more general nonlinear canonical transformations [97]. Some general results on canonical transformations are reviewed in appendix C.1.…”
Section: Optimized Basis Setmentioning
confidence: 99%
“…Finally, in the approach taken here, it will be possible to consider transformations that mix the two Hilbert spaces, which will be further explored. As special cases of transformed basis sets, one could consider Bogoliubov transformations [5][6], local canonical transformations [33][34], or more general nonlinear canonical transformations [35]. Some general results on canonical transformations are reviewed in appendix A.…”
Section: Optimized Basis Setmentioning
confidence: 99%
“…Thus, for n=6, the partial solutions of the Clifford equation can be represented with the help of six antisymmetric matrixes. It should be noted that the specified formalism is closely connected with the Bogolyubov-Valatin transformations [30]. It can be shown that for n=8, partial solutions of the Clifford equation can be represented with the help of 8 matrixes: seven antisymmetric matrixes and an one symmetric matrix [5], [3, p. 77, Section 14.4(eng), p. 211(88), Section 14.4 (rus)], [2, p. 88, Section 14.4].…”
Section: Complex Orthogonal Transformations Involutionsmentioning
confidence: 99%